Influence of loading and cracks on carbonation of RC elements made of different concrete types. (10th March 2018) - Wang, Xiao-Hui; Val, Dimitri V.; Zheng, Li; Jones, M. Roderick
Highlights: Carbonation of loaded and unloaded PC, FA and GGBS concretes was experimentally studied. Both compressive and tensile stresses had major influence on concrete carbonation. Loading had much larger effect on carbonation of FA and GGBS concretes. Casting position, cracking and stirrups affected carbonation. Abstract: Accurate prediction of concrete carbonation is important for the correct assessment of both durability and environmental impact of reinforced concrete (RC) structures. Loading applied to a RC structure and concrete cracking caused by this loading may significantly affect the concrete carbonation process. However, so far these factors have received little attention of researchers, especially this concerns 'green' concretes, i.e. concretes in which Portland cement (PC) is partially replaced by supplementary cementitious materials such as fly ash (FA) and ground granulated blast-furnace slag (GGBS). Thus, the aim of the study presented in the paper was to experimentally investigate the influence of static loading and associated concrete cracking on carbonation of RC elements made of PC concretes and 'green' concretes containing significant amounts FA and GGBS. For this purpose, six concrete mixes with two water/binder (w/b) ratios (0.40 and 0.55) and different proportions of PC, FA and GGBS were prepared. The mixes were used to cast twelve RC beams (100 × 120 × 900-mm) and a larger number of 100-mm concrete cubes. The beam specimens were loaded in four-point bending to produce flexural cracks of maximum width of either 0.1 mm or 0.3 mm. The loaded beam specimens along with unloaded cube specimens were then placed into a carbonation chamber and subject to accelerated carbonation for 120 days. After that the carbonation depths in the beams and cubes were measured. Results of the tests show a significant effect of load induced stresses (both tensile and compressive) on the carbonation resistance of the concretes, especially of 'green' concretes. The influence of cracking on concrete carbonation was also observed and discussed in the paper.